Digital leadership, it support, and organizational learning capability: The mediating role of knowledge sharing - Rahman, Md. Habibur; Shin, Jin Kyo; Makhammatjonovich, Mamadaliev Mamirjon (International Journal of Management and Sustainability, 2025)
The accelerating pace of digital transformation and globalization has placed significant pressure on organizational innovation sustainably. This study investigates the extent to which Digital Leadership (DL), IT Support (ITS), and Knowledge Sharing (KS) contribute to the development of Organizational Learning Capability (OLC). The research was conducted in South Korea’s Daegu Industrial Area, with a focus on the automobile industry. The survey consisted of a total of 355 respondents, providing insights into their perceptions of IT support, digital leadership, and knowledge-sharing practices within their organizations. The study employed partial least squares structural equation modeling (PLS-SEM) to analyze research data. Grounded in the Resource-Based View (RBV) theory, the study found that both DL and ITS substantially and positively influence KS, which in turn substantially influences OLC. Moreover, the analysis revealed that KS fully mediates the relationships between DL and OLC, as well as between ITS and OLC. These findings emphasize the central role of KS in boosting sustainable OLC. The findings provide meaningful understanding for managers seeking to align KS initiatives with their organizations’ strategic objectives. By simultaneously examining the interrelationships among DL, ITS, KS, and OLC, this study extends prior empirical research and provides actionable recommendations for strengthening sustainable OLC in digitally advanced business settings. The study provides useful insights to foster OLC by replacing old and obsolete learning methods to remain sustainably competitive in terms of innovation and creativity. However, the digital work environment of South Korea may limit the applicability of the findings to other work environments.